RISIKO PERBANKAN DAN PROFITABILITAS - Pradnyawati, Sagung Oka; Sudana, I Putu; Sujana, I Ketut (Buletin Studi Ekonomi; VOL.22.NO.1. FEBRUARI 2017 (PP 1-112), 2017)
This research aims to get empirical evidence about influence of credit risk, operational risk, and liquidity risk on profitability. This research adopts goal setting theory and risk and return theory. Empirical studies conducted as banking company listed on Indonesia Stock Exchange on period 2011-2015 with 112 company years as a sample was that obtained using purposive sampling technique. In this reseacrch has using secondary data obtained from the official website of the Indonesia Stock Exchange. The analysis technique used in this study is the technique of regression analysis support with tools statistical applications product and service solutions version 16. The results showed that (1) NPL have a negative effect on profitability, (2) BOPO have a negative effect on profitability, (3) LDR have a positive effect on profitability.